2014
DOI: 10.1155/2014/498276
|View full text |Cite
|
Sign up to set email alerts
|

Melanins: Skin Pigments and Much More—Types, Structural Models, Biological Functions, and Formation Routes

Abstract: This review presents a general view of all types of melanin in all types of organisms. Melanin is frequently considered just an animal cutaneous pigment and is treated separately from similar fungal or bacterial pigments. Similarities concerning the phenol precursors and common patterns in the formation routes are discussed. All melanins are formed in a first enzymatically-controlled phase, generally a phenolase, and a second phase characterized by an uncontrolled polymerization of the oxidized intermediates. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
462
0
16

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 441 publications
(483 citation statements)
references
References 257 publications
(303 reference statements)
5
462
0
16
Order By: Relevance
“…We performed an extensive study, using elemental analysis, UV/infrared absorption spectrophotometry, measurement of the zeta potential, and solid-state NMR analysis (43)(44)(45)(46), in order to identify the chemical characteristics of A. infectoria melanin (see the supplemental material) and found that A. infectoria melanin-derived pigments exhibited substantial absorption in the UV spectrum and none in the visible light spectrum, as well as diverse spectroscopic characteristics shared with other melanins described to date (47), including A. alternata DHN-melanin (see the supplemental material). To ascertain the chemical nature of the melanin, we used specific inhibitors of the DHN-melanin (pyroquilon) and of the DOPA-melanin (glyphosate) synthetic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…We performed an extensive study, using elemental analysis, UV/infrared absorption spectrophotometry, measurement of the zeta potential, and solid-state NMR analysis (43)(44)(45)(46), in order to identify the chemical characteristics of A. infectoria melanin (see the supplemental material) and found that A. infectoria melanin-derived pigments exhibited substantial absorption in the UV spectrum and none in the visible light spectrum, as well as diverse spectroscopic characteristics shared with other melanins described to date (47), including A. alternata DHN-melanin (see the supplemental material). To ascertain the chemical nature of the melanin, we used specific inhibitors of the DHN-melanin (pyroquilon) and of the DOPA-melanin (glyphosate) synthetic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Melanins in fungi and other microorganisms are derived from tyrosine via 3,4-dihydroxyphenylalanine (DOPA), γ-glutaminyl-3,4-dihydroxybenzene (GDHB) or catechol, and 1,8-dihydroxynaphthalene (DHN) (Bell and Wheeler, 1986). It is believed that the precursor in plants is catechol, caffeic, chlorogenic, protocatechuic, or gallic acid (Solano, 2014), but there is not yet evidence. The structures of melanins have rarely been studied due to the difficulties in the isolation of melanins from natural sources and the poor solubility of the pigments.…”
Section: Introductionmentioning
confidence: 99%
“…Han et al (2015) analysed the presumed relation and interaction between the ovine KIT and MITF gene expression and whether it affects the colour of sheep wool. The MITF gene codes for a protein microphthalmia-associated transcription factor, the most obvious function of which is the development of melanocytes; the MITF expression is correlated with the pigment accumulation in melanocytes (Steingrímsson et al, 2004). Causative mutations in MITF are mostly recognized to be involved in metabolic disorders in melanocytes, affecting the pigment content of the skin, hair, and eyes.…”
Section: The Microphthalmia-associated Transcription Factormentioning
confidence: 99%
“…These cells are specialized in producing melanins -pigments protecting organisms from ultraviolet radiation (Solano, 2014). Melanins are divided into eumelanins (black/brown, pigmented phenotype) and pheomelanins (red/yellow, non-pigmented phenotype).…”
Section: Introductionmentioning
confidence: 99%